Isolation and characterization of Linocin M18, a bacteriocin produced by Brevibacterium linens. - Valdés-Stauber, N (1994)
Brevibacterium linens M18, isolated from red smear cheese, produces a substance that inhibits the growth of Listeria spp. and several coryneform and other gram-positive bacteria. No gram-negative bacteria were inhibited. The substance is heat labile, sensitive to proteolytic enzymes, and stable between pH 3 and 12. High levels of this bacteriocin, named Linocin M18, were obtained in the stationary growth phase. Linocin M18 was purified by ultrafiltration, ultracentrifugation, and gel filtration chromatography. In its native form, it is a proteinaceous aggregate with a high molecular weight. Fractions with Linocin M18 activity contained particles of 20 to 30 nm in diameter. The bacteriocin consists of a single protein subunit with a molecular mass of 31 kDa and an isoelectric point of 4.5 N-terminal sequence analysis yielded Met-Asn-Asn-Leu-Tyr-Arg-Glu-Leu-Ala-Pro-Ile-Pro-Gly-Pro-Ala-Ala-Ala-Glu- Ile. Significant homology with published sequences was lacking.